Pembelajaran Berbasis Audio Visual pada Materi Teks Biografi di Kelas X SMA - Khadijah, Khadijah; Safina, Nila; Rita, Rita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
This study aimed to develop and assess the validity and feasibility of audio-visual-based learning media for Listening Biography Texts in Class X SMA/MA during the Covid-19 period. The development process followed the model proposed by Stephen M. Alessi and Trollip, encompassing planning, design, and development stages. The results revealed that the audio-visual-based learning materials obtained high feasibility ratings from material experts (82% "very feasible" and 78% "adequate") and learning media experts (90% "very eligible" and 77% "eligible"). The developed audio-visual-based learning media proves to be suitable for instructional use, addressing the issues of limited media and low student engagement during the pandemic. This study contributes to the enhancement of effective learning strategies amidst challenging circumstances.